Tensions Between Pedagogical Knowledge in Evaluation and Teaching Practice in Vulnerable Schools of the Arica Commune - Roberts-Sánchez, Katherine; Rodríguez-Gómez, David; Silva, Patricia (Revista Electrónica Educare, 2020)
This article analyzes the evaluative practices of teachers working in fifteen vulnerable schools in the Arica Commune, located in the extreme north of Chile. This is a qualitative study whose data has been collected through semi-structured interviews and discussion groups. To process the collected information, content analysis was performed following the guidelines of the Grounded Theory. The results show that, although teachers have been transitioning from a traditional evaluative practice to an increasingly authentic one throughout their professional career, there are still tensions between their discourse on evaluation and their evaluative practices. The evidence of these tensions recommends connecting the educational and evaluative experience of the classroom with relevant issues in the student’s life. The aim is to promote evaluative practices sensitive to school contexts among teachers, incorporating affective resources in their implementation.